ANCHOR: A Technical Approach to Monitor Single-Copy Locus Localization in Planta - Meschichi, Anis; Ingouff, Mathieu; Picart, Claire; Mirouze, Marie; Desset, Sophie; Gallardo, Franck; Bystricky, Kerstin; Picault, Nathalie; Rosa, Stefanie; Pontvianne, Frédéric (Frontiers in Plant Science, 2021)
Together with local chromatin structure, gene accessibility, and the presence of transcription factors, gene positioning is implicated in gene expression regulation. Although the basic mechanisms are expected to be conserved in eukaryotes, less is known about the role of gene positioning in plant cells, mainly due to the lack of a highly resolutive approach. In this study, we adapted the use of the ANCHOR system to perform real-time single locus detection in planta. ANCHOR is a DNA-labeling tool derived from the chromosome partitioning system found in many bacterial species. We demonstrated its suitability to monitor a single locus in planta and used this approach to track chromatin mobility during cell differentiation in Arabidopsis thaliana root epidermal cells. Finally, we discussed the potential of this approach to investigate the role of gene positioning during transcription and DNA repair in plants.